Urgensi Pendidikan Bela Negara di Era Globalisasi - Muh Ilham; Galih Wahid Hasyim; Jon Sastro (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2025)
Globalization has transformed the way individuals and communities interact, access information, and construct social and cultural identities. The increasingly rapid and massive flow of information provides benefits but also opens opportunities for non-traditional threats that may erode national values. This condition demands an educational response to strengthen citizens’ capacity in safeguarding ideological and socio-cultural sovereignty. National defense education plays a strategic role amid the dynamics of globalization, which is marked by the influence of foreign cultures, the spread of disinformation, radicalism, and cyber threats that could weaken national identity. This study aims to examine the relevance and urgency of national defense education in equipping young generations with the values, attitudes, and skills required to preserve national unity and respond to global influences. The research method used is a comprehensive literature review, analyzing books, scientific journals, and previous studies. The findings show that national defense education is essential in fostering patriotism, strengthening national character, and preparing young people to face ideological, social, and digital threats. It also enhances the understanding of Pancasila values, national history, and civic responsibilities, while increasing resilience against modern challenges such as disinformation and digital radicalism. Thus, national defense education becomes a fundamental foundation for maintaining Indonesia’s sovereignty and continuity in a complex global era, while contributing to enrich the concept of national defense to be more relevant to contemporary dynamics and digital transformation.